PENGARUH PENGEMASAN VAKUM TERHADAP KUALITAS BANDENG PRESTO SELAMA PENYIMPANAN - Purnamayati, Lukita; Wijayanti, Ima; Dwi Anggo, Apri; Amalia, Ulfah; Sumardianto, Sumardianto (Jurnal Teknologi Hasil Pertanian, 2018)
Softbone milkfish is a fishery product that easily damaged during storage. One of the efforts to inhibit thedamage of softbone milkfish was using vacuum packaging. The purpose of this study was to determine thechanges quality of softbone milkfish which were vacuum packed during storage at room temperature. Freshmilkfish was heating with high pressure by using a pressure cooker. Softbone milkfish was then stored at roomtemperature for six days. Analysis was carried out every three days for the parameters of free fatty acids, TVBN,and organoleptics. The results showed that the number of free fatty acids and TVBN increased during storage.Free fatty acids and TVBN of softbone milkfish with vacuum packaging after sixth days of storage were 2.95%and 15.95 mgN/100g, respectively. This value was lower than the non-vacuum softbone milkfish. Based onorganoleptic analysis, softbone milkfish with vacuum packaging was still suitable for consumption until the thirdday of storage. This showed that vacuum packaging can extend the shelf life of softbone milkfish.